α-TubK40me3 is required for neuronal polarization and migration by promoting microtubule formation - Xie, Xuan; Wang, Shaogang; Li, Mingyi; Diao, Lei; Pan, Xingyu; Chen, Jijun; Zou, Weiguo; Zhang, Xu; Feng, Wenfeng; Bao, Lan (Nature communications, 2021)
Tri-methylation on lysine 40 of α-tubulin (α-TubK40me3) is a recently identified post-translational modification involved in mitosis and cytokinesis. However, knowledge about α-TubK40me3 in microtubule function and post-mitotic cells remains largely incomplete. Here, we report that α-TubK40me3 is required for neuronal polarization and migration by promoting microtubule formation. α-TubK40me3 is enriched in mouse cerebral cortex during embryonic day (E)14 to E16. Knockdown of α-tubulin methyltransferase SETD2 at E14 leads to the defects in neuronal migration, which could be restored by overexpressing either a cytoplasm-localized SETD2 truncation or α-TubK40me3-mimicking mutant. Furthermore, α-TubK40me3 is preferably distributed on polymerized microtubules and potently promotes tubulin nucleation. Downregulation of α-TubK40me3 results in reduced microtubule abundance in neurites and disrupts neuronal polarization, which could be rescued by Taxol. Additionally, α-TubK40me3 is increased after losing α-tubulin K40 acetylation (α-TubK40ac) and largely rescues α-TubK40ac function. This study reveals a critical role of α-TubK40me3 in microtubule formation and neuronal development. Post-translational modifications of tubulins regulate microtubule properties and neural development. Here, the authors report that one such post-translational modification, α-TubK40me3, is required for neuronal polarization and migration by promoting microtubule formation.